Utilization of β-farnesene distillation and evaporation residues for the production of green polyol and its subsequent conversion to polyurethane foams - Capeto, Paula (2021)
Valorization of β-farnesene distillation and evaporation residue (FDR) through transformation into bio-based polyols. Production of rigid polyurethanes using green methodologies.